Environmental effects of acid mine drainage and rehabilitation options at closed mine site: a case study - Konanç, Mustafa Umut; Değermenci, Gökçe Didar (Springer Science and Business Media LLC, 2024)
Irregular waste storage at closed mine sites poses severe environmental problems. This study evaluates the concentrations and effects of trace elements released into the environment by mining activity by analyzing soil, water, and sediment samples taken from a copper mining site. According to the data, acidic mine drainage was the main cause of the high concentrations of trace elements in the soil and sediments, including arsenic (As), cadmium (Cd), lead (Pb), and copper (Cu). The concentrations of As, Cd, Pb, and Cu in soil and sediments were 2734-times, 1189-times, 157-times and 32 times higher, respectively, in comparison to the background values of averaged concentrations of these elements in the upper crust. Geological and statistical studies indicate that the primary constituents of these pollutants are chalcopyrite and pyrite derivatives present in the primary rock structure. Using water analysis data from 2011 to 2020, the release of essential trace element into water was investigated to monitor the environmental effects of acidic mine drainage (AMD) from the closed Kuvarshan copper mine in the Artvin region of Turkey. This study demonstrates that trace elements concentrations may change according to local and seasonal factors and highlights the importance of conducting routine environmental monitoring studies.
Keywords: Geologic Sediments; Soil; Turkey; Metals, Heavy; Soil Pollutants; Industrial Waste; Acids; Mining; Water Pollutants, Chemical; Copper; Environmental Monitoring; Arsenic; Trace Elements